Islamic Store Brand Engagement and Customer Loyalty Relationship - Chandra Warsito; Nida Umi Farhah; Wiwiek Rabiatul Adawiyah; Norailis Ab Wahab (Faculty of Islamic Economics and Business at UIN RadenIntan Lampung Indonesia, 2024)
Non-Indexed Publication